Identity of Speech Community in Biak Numfor Papua: Anthropolinguistic Study Perspective - Hugo Warami (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
Language and cultural richness of Biak Numfor in Papua is part of a national identity characterized by "Bhineka Tunggal Ika" (Unity in Diversity) as the basic foundation in building Indonesia. This article aims to reveal the identity system of speech in a community of Biak Numfor, Papua from an anthropolinguistic perspective. While the theoretical approach is an exploration of anthropolinguistic theory, the methodological approach is a descriptive one with an explanative dimension. From an anthropolinguistic perspective, this study seeks to apply scientific principles of socio-cultural data and adapt the steps in scientific studies to other fields of science. This study follows several stages, including providing data, analyzing data, presenting the results of the analysis. As a result, we holistically identify problems that refer to the system of phonology, naming and dialect differences, morpheme interference, syllable patterns, phoneme series, numeralia, unit of measurement, time unit, language vitality, language and culture migration, ritual tradition, dou tradition, faith, social unity and place of living, social stratification, marriage, kinship, legal culture (adat), legal sanctions, and forest ecology. The practical implication of this study is that it can be used as a basic reference in human resource development in Biak Numfor Regency. In addition, since anthropolinguistic theory has not been able to codify all language and socio-cultural systems, we suggest that theoretical collaboration in other fields is needed to complement the development of the theory.